Exercise domain profile through pulmonary gas exchange response during kendo practice by men - Sancassani, Andrei [UNESP]; Pessoa Filho, Dalton M. [UNESP] (Int Scientific Literature, Inc, 2014)
Background & Study Aim: The metabolic rate demanded during the practice of kendo techniques has not been reported, despite of it importance to physical training program. This study aimed to characterize exercise intensity during kendo practice based on pulmonary gas exchange profiles.Material & Methods: Nine skilled male athletes (29.7 +/- 7.8 years old, 174.9 +/- 9.1cm, 82.1 +/- 14.9kg body weight) underwent the following protocols: (1) body composition via DXA, (2) progressive treadmill test to assess (V) over dotO(2)max, gas exchange threshold (GET) and respiratory compensation point (RCP), and (3) 11 types of warm-ups using kendo techniques and 31 types of kendo waza. The techniques were performed twice, with a 24h break in between. The (V) over dotO(2) value was obtained using K4b2 (COSMED (R)) technology, and heart rate (HR) was recorded by 420sd (Polar (R)) frequencimeter.Results: The (V) over dotO(2) profile reached 84.7 +/- 13.5% (V) over dotO(2)max and 85.3 +/- 17.2% (V) over dotO(2)max at the end of warm-up and waza protocols, respectively. (V) over dotCO(2) showed the same profile: 83.5 +/- 9.40% and 81.1 +/- 13.7% (V) over dotCO(2)max for warm-up and waza. However, HR (97.8 +/- 3.3% and 103.4 +/- 3.6% HRmax) and (V) over dot(E) (90.1 +/- 15.6 and 107.8 +/- 13.2% (V) over dot(E)max) elicited values that were trunked to maximum rates at the end of warm-up and waza. The RER values at the end of warm-up (1.19 +/- 0.15) and waza (1.16 +/- 0.05) were greater than 1.1. All variables did not differ from their respective maximum rate values at the end of warm-up and waza (p <= 0.05, ANOVA with Tukey as post-hoc).Conclusions: Thus, (V) over dotO(2) and (V) over dotCO(2) profiles classified the kendo practice as a heavy domain exercise, while HR, E and RER classified it as a heavy-to-severe domain exercise.
Keywords: martial arts; oxygen; during exercise; continuous heart rate monitoring; skill performance; exercise classification